TINJAUAN HADIST DALAM PERSPEKTIF SUNNI DAN SYI’AH - Andrean, Seka (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2021)
The majority of muslims view hadith as the root of islam’s second teaching after the Qur’an. The focus of this research is on the hadith review in the perspective of sunni and shi’ah. This analysis concluded that the two peoples agreed that hadith was used as the root of the second law after the Qur’an. But in each of these people, there are differences about the acceptance of hadiths that can be used as arguments. The Sunnis define hadith is everything is encoded by Rasullulah SAW both in its words, deeds and statutes. Then the Shi’ite people define hadith as sunnah, because for them the hadith is not just a speech, an act or a statute of Rasullulah SAW alone. In the classification of hadith, based on its quality Sunni divides hadith into hadith saheeh, hadith hasan, and hadith dha’if. While shia divide hadith into hadith saheeh, hadith hasan, hadith muwassaq, and hadith dha’aif. Although the two have quite strong differences, but in the real world man will still need a hadith in his life. Then in saheeh. Sunnis consider that companions have a just nature and Shi’a considers that companions are wicked human beings, for for them a friendship with the Prophet SAW does not determine that man has a nature in kindness and honesty.